(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the transformation of the family institution in the context of digital society from a socio-philosophical perspective. The rapid development of the Internet, mobile communication technologies, and social media has significantly influenced family relations, communication patterns, and the formation of social roles. The research is based on theoretical analysis, literature review, and comparative analysis to examine the impact of digital technologies on the family institution. Empirical findings from international organizations such as OECD, UNICEF, and Pew Research Center were examined and summarized. The results indicate that digital technologies expand opportunities for family communication and maintaining social ties, while simultaneously creating challenges such as excessive screen time, cyberbullying, and social comparison. The author argues that in the digital era the family institution does not disappear but rather adapts and transforms through new forms of communication and social interaction.